1951
DOI: 10.1111/j.1365-2621.1951.tb17387.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF EXPERIMENTBLLY INOCULATING CANNED BREAD WITH SPORES OF CLOSTRIDIUM BOTULINUM AND BACILLUS MESENTERICUSa,b

Abstract: MATERIALSTwo different formulae were used for preparing the bread doughs, one having a higher pH and moisture content (the old formula) than the other (the new formula);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1951
1951
2004
2004

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The general range of these pH limits is similar to that previously reported, for diverse American strains, in a variety of foods (Thompson & Tanner, 1925) as well as in bread media (Bever & Halvorson, 1947 ;Kadavy & Dack, 1951). There is, therefore, no reason to suppose that there is any unusual reaction to pH, either in British strains of Cl.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The general range of these pH limits is similar to that previously reported, for diverse American strains, in a variety of foods (Thompson & Tanner, 1925) as well as in bread media (Bever & Halvorson, 1947 ;Kadavy & Dack, 1951). There is, therefore, no reason to suppose that there is any unusual reaction to pH, either in British strains of Cl.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, there were changes in pH with no clearly defined pattern, purely as a result of incubation. Analogous changes in pH during incubation, with bread simply stored in cans, were recorded by Kadavy & Dack (1951).…”
Section: Control Of P H During the Experimentsmentioning
confidence: 99%
“…232 Subsequent studies confirmed that canned bread could support growth and neurotoxin production and determined that the conditions necessary for the safe production of this product would be a pH < 5.4 and a moisture content of 35% (corresponding to an a w of ∼0.95). 135,232,252 However, increasing the pH of the product resulted in toxigenesis. Growth and toxin production was observed in inoculated canned bread with a pH of 5.8 and a moisture content >36% and in canned steamed chocolate nut bread with a pH of 6.8 and 36% moisture.…”
Section: B Associated Outbreaksmentioning
confidence: 99%
“…However, propionic acid or its salts at permitted maximum levels (2000 ppm), were ineffective in preventing the toxin production of C. botulinum in canned bread (pH 5.4) or in sterile bread crumbs. 24,135 While higher levels of propionates (6%) may delay the growth of C. botulinum, such high levels, if legally permitted, would result in off flavors and the sensory rejection of baked products. However, since most bakery products, with the exception of sourdough, have pH values >5.0, chemical presevatives lose their antimicrobial effect, due to their low dissociation constants.…”
Section: Control Measuresmentioning
confidence: 99%
“…Whether the limiting moisture activities for the different foods are exactly the same, however, has not yet been proven. Some studies related to the moisture limitations on spore germination have been reported for canned bread (Halvorson, 1949;Kadavy and Dack, 1951;Ulrich and Halvorson. 1948-49;Wagenaar and Dack, 1954), beef liver paste (Williams, 1950 and, canned cheese spreads (Wagenaar and Dack, 1955), and for such dehydrated meats as beef and pork (Segalove and Dack, 1951).…”
Section: Megatheriummentioning
confidence: 99%